2013
DOI: 10.3109/14764172.2013.780448
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment of CO2fractional laser, pulsed dye laser, and triamcinolone acetonide injection for refractory keloid scars on the upper back

Abstract: Keloids and hypertrophic scars are common lesions, which typically present as a cosmetic concern; however, they also can cause significant pruritus and pain. These lesions pose as a particular therapeutic challenge among clinicians due to a lack of complete knowledge of the formation of keloids and hypertrophic scars. Multiple treatments are widely accepted, yet all have shown limited benefit. In this case, we describe the treatment combination of the Affirm CO2 fractional laser (10 600 nm, Cynosure), Cynergy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Contrastingly, Martin et al [5] combined treatment with a CO 2 fractional laser, a Cynergy pulsed-dye laser, and triamcinolone acetonide injections to treat keloids, and they reported excellent results with minimal flatness, diminished pruritus, and lighter pigmentation. Son et al [7] showed that 42% of patients reported ≥75% improvement after treatment with a 578 nm copper bromide laser combined with intralesional corticosteroid injections.…”
Section: Methodsmentioning
confidence: 99%
“…Contrastingly, Martin et al [5] combined treatment with a CO 2 fractional laser, a Cynergy pulsed-dye laser, and triamcinolone acetonide injections to treat keloids, and they reported excellent results with minimal flatness, diminished pruritus, and lighter pigmentation. Son et al [7] showed that 42% of patients reported ≥75% improvement after treatment with a 578 nm copper bromide laser combined with intralesional corticosteroid injections.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, it has been reported in the literature that radiotherapy is the most efficacious treatment available in severe cases of keloids, combined with surgical excision [6,35], and flap reconstruction. Other more non-invasive approaches may consist of combining PDL, fractional CO 2 laser and TAC [101]. …”
Section: Special Casesmentioning
confidence: 99%
“…Keloids are distinguished from HTS by their extension beyond the original sites of trauma, persistence for a prolonged period, rare resolution without treatment, and recurrence after excision. HTS do not extend beyond the initial site of injury and slowly reduce in size, ultimately resolving over a period with low recurrence rates . HTS and keloids are a challenge for the treating physician because of the weak response to treatment, recurrences after treatment, and side effects associated with the treatment modalities .…”
Section: Introductionmentioning
confidence: 99%
“…not extend beyond the initial site of injury and slowly reduce in size, ultimately resolving over a period with low recurrence rates. 3 HTS and keloids are a challenge for the treating physician because of the weak response to treatment, recurrences after treatment, and side effects associated with the treatment modalities. 4,5 There is no universally accepted method of treatment, which will lead to complete resolution of HTS or keloids.…”
mentioning
confidence: 99%